Carga aérea e competitividade da indústria Brasileira - José Tavares de Araújo Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The paper discusses the role of air cargo as a competitive instrument for Brazilian manufacture, examining foreign trade data broken down by chapters of the Harmonized System (HS), and comparing the share of air cargo with other economies. The analysis was performed in two steps. The first identified the similarities and differences between the air cargo profile of Brazilian foreign trade and the selected economies. The second examined the evolution of Brazilian exports and imports in the chapters that followed the contemporary standards regarding air cargo use, and those which revealed a divergent behavior. The comparison with other economies has shown that many Brazilian firms behave according to the predictions of economic theory, although there are important performance disparities between different industries. Interviews with some of the major air cargo users revealed that the prospects of this mode of transportation in Brazil not only depend on continued investment in maintenance and expansion of terminals, but also on reshaping the national air network, focusing on ties with other South American countries.
Keywords: F1; F14; 330; air cargo; competitiveness